2017
DOI: 10.1159/000481404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gastric Cancer Surgery in Elderly Patients

Abstract: Objectives: This study aimed to investigate the validity of gastric cancer surgery in elderly patients. Methods: A total of 544 patients who underwent elective gastrectomy for gastric cancer were divided into an elderly group (age ≥75 years, n = 171) and a control group (age <75 years, n = 373). The clinicopathological data of the patients were reviewed. Results: The overall morbidity rate (26.3 vs. 16.1%, p = 0.005) and the incidence rate of anastomotic leakage (6.4 vs. 1.6%, p = 0.003) were significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The overall complication rate after gastrectomy in GC patients over 80 years of age was reported to be 30.8% in a recent study (18). The present study demonstrated that complications with a Clavien-Dindo classification≥grade II were observed in 24.8% of patients, which is consistent with the results of previous reports on elderly GC patients (19,20). In previous studies analyzing elderly GC patients, the elderly group tended to have lower ASA-PS, hemoglobin levels, and serum albumin levels than the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The overall complication rate after gastrectomy in GC patients over 80 years of age was reported to be 30.8% in a recent study (18). The present study demonstrated that complications with a Clavien-Dindo classification≥grade II were observed in 24.8% of patients, which is consistent with the results of previous reports on elderly GC patients (19,20). In previous studies analyzing elderly GC patients, the elderly group tended to have lower ASA-PS, hemoglobin levels, and serum albumin levels than the control group.…”
Section: Discussionsupporting
confidence: 92%
“…However, this database included all stages of gastric cancer surgical cases and revealed only short-term outcomes without survival data after surgery for gastric cancer. In other reports for elderly gastric cancer patients, the patient selection was biased, and the number of patients was limited [7][8][9]. The present data were specific for elderly patients with Stage I gastric cancer, which allowed us to analyze various factors associated with short-and long-term outcomes for various age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is important that a preoperative evaluation be performed to see if a patient can tolerate the stress caused by surgery. Several authors reported acceptable postoperative morbidity rates after gastric cancer surgery in elderly patients, although they were higher than those of younger patients [15,16], while others reported that postoperative morbidity rates were similar between elderly and nonelderly patients [17]. Regarding long-term outcomes after gastric cancer surgery, we previously reported that the outcomes of elderly patients were relatively worse than those of younger patients; however, the difference was not statistically significant [16].…”
Section: Discussionmentioning
confidence: 79%
“…Several authors reported acceptable postoperative morbidity rates after gastric cancer surgery in elderly patients, although they were higher than those of younger patients [15,16], while others reported that postoperative morbidity rates were similar between elderly and nonelderly patients [17]. Regarding long-term outcomes after gastric cancer surgery, we previously reported that the outcomes of elderly patients were relatively worse than those of younger patients; however, the difference was not statistically significant [16]. It has also been reported that the overall survival rate of elderly patients with gastric cancer treated with surgery is significantly higher than that of those given only the best supportive care, especially in cases of advanced cancer [18].…”
Section: Discussionmentioning
confidence: 99%